Effect of a serious game JeStiMulE in emotion recognition of Moroccan autistic children - MAMMAD, Khaoula (Journal of Educational, Health and Community Psychology, 2018)
Human beings can express their emotions in different ways such as facial expressions, bodily expressions, prosody, or language. However, ASDs are life-long neurodevelopmental disorders characterized by varying levels of social and communicative defcit. The influence of a "serious game" named "JeStimule" on improving the recognition of facial emotions in children with autism. We have 17 autistic children with different characteristics recruited for a cross-sectional study. The level of language comprehension and academic learning is slightly heterogeneous. We have more boys than girls with an average age of 11.23. It has been concluded that children have a gradual ease in recognizing the following emotions: Happiness, surprise, sadness, anger, pain, fear, but the result of the 3 emotions that is lacking (Neutral, funny face, Disgust) was unsatisfactory and very difficult for the child to understand. This type of educational game for children with autism is effective and important for this child profile, to improve these skills to recognize the emotions of others. However, there is a need to carry out more research to put in place specific educational games in the context of a Moroccan child. Autism recognition of emotions is a cognitive remediation area of great interest to this population.